Drug-induced anaphylaxis during general anesthesia in 14 tertiary hospitals in Japan: a retrospective, multicenter, observational study - Horiuchi, Tatsuo (J Anesth, 2021)
Since perioperative anaphylaxis occurs suddenly, and it can be life-threatening, anesthesiologists need to have sufficient knowledge of the epidemiology of perioperative anaphylaxis and appropriate coping strategies to deal with it. Recent studies conducted in Western countries reported the characteristics of perioperative anaphylaxis in each country. However, there are few studies of perioperative anaphylaxis in Japan. To bridge the gap between Japan and other countries, the data of 46 anaphylaxis patients at Gunma University Hospital and 13 neighboring hospitals between 2012 and 2018 were collected and analyzed. The recently developed clinical scoring system was combined with a skin test to include only cases with a definite diagnosis. The most common causative agents were sugammadex, followed by rocuronium, cefazolin, and antibiotics other than cefazolin. Furthermore, the characteristics of anaphylaxis for each causative drug were identified. Time from drug administration to appearance of the first symptom was the longest in the cefazolin group. The incidence of canceled operation was the highest in the rocuronium group. Although it is unclear whether the results of this study can apply to Japan as a whole, the information about the agents responsible for perioperative anaphylaxis and the characteristics of anaphylaxis due to each agent would be helpful to anesthesiologists. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1007/s00540-020-02886-5.